Defect detection in high pressure die casting product using image processing technology - Wahab, Md Saidin (2003)
In this thesis an Automated Visual Inspection (AVI) system for ckl'eel dL'lc'L'li"i1 ('( 111~h Pressure Die Casting (HPDC) product has been dcveloped, The sy,lelll i, l'i1;lblin~ 1(\ detect external structural defects of the product particularly for crack and Iwk. This lhesi, also describes detailed procedures based on image processing technnl,,~} IIhich include enhancement/preprocessing, segmentation, codingifeature extractinn and I III age analysis/classification/interpretation, The commercial Matlab image processing kls been used to implement these procedures, An intelligent approach based on mllrpllOlog~ and fuzzy logic is proposed to detect such structural defects on the surface. The proposed method has been implemented and tested on a number of 111'1)(' I'rllducl. The results suggest that the method provide an accurate identification tn lhe dekelS and be extended for further application, The results also suggest that the system 1I('rk lIell enough to help die casting manufacturer to improve the value or die Glsling I,rllduc\ lil;11 they can obtain from automated inspection system, A few suggestions have been discussed for future research to address the limiwlillns of this research.